Economic growth in Colombia: an empirical approximation founded in human capital (1960-2009) - Cuenca-Coral, Maria Esperanza; Penagos-Montoya, Ignacio (Universidad Pedagógica y Tecnológica de Colombia, 2014)
The aim of this paper is to specify an empirical model based on theoretical arguments, quantifying the influence of human capital, measured through a set of variables that reflect the health and education behavior on the outcome of economic growth observed for Colombia, between 1960 and 2009. The authors review the literature on economic growth and human capital, represented by health and education, so that, with the sources of information available in Colombia, they do a selection of data that allows the collection of variables that reflect and quantify the transmission channels suggested by existing theory. Finally, they specify an empirical model that estimates the theoretical relationship between human capital and economic growth.